2016
DOI: 10.1371/journal.pone.0168379
|View full text |Cite
|
Sign up to set email alerts
|

First Molecular Characterization of Bovine Leukemia Virus Infections in the Caribbean

Abstract: Bovine leukemia virus (BLV) is a retrovirus that causes enzootic bovine leucosis. To investigate the presence and genetic variability of BLV in the Caribbean for the first time, we preformed fluorescence resonance energy transfer (FRET)-PCR for the pol of BLV on DNA from whole blood of cattle from Dominica, Montserrat, Nevis and St. Kitts. Standard PCRs with primers for the env were used for phylogenetic analysis of BLV in positive animals. We found FRET-PCR positive cattle (12.6%, 41/325) on Dominica (5.2%; 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…In Australia, only genotype-1 was detected [ 90 ]. In North America, genotypes −1, −3, and −4 have been detected in the USA [ 86 , 143 , 145 ], and genotype-1 was reported in the Caribbean [ 146 ]. In Central America, genotypes −1 and −5 were detected in Costa Rica [ 143 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, only genotype-1 was detected [ 90 ]. In North America, genotypes −1, −3, and −4 have been detected in the USA [ 86 , 143 , 145 ], and genotype-1 was reported in the Caribbean [ 146 ]. In Central America, genotypes −1 and −5 were detected in Costa Rica [ 143 ].…”
Section: Introductionmentioning
confidence: 99%
“…Strains identified in our study from China are identified with filled circles (•). Genotypes shown on the right are according to Yang et al (2016b). The numbers at the branches show bootstrap support (1,000 replicates).…”
mentioning
confidence: 99%
“…previous study (Yang et al, 2016b). Amplicons were gel purified with the QIAquick Gel Extraction Kit and sequenced at the Genomic Sequencing Laboratory (GBI, Shanghai, China).…”
mentioning
confidence: 99%
“…For example, a predicted RFLP pattern of BLV env sequence of AY185360 using three endonucleases, Bcl I, Hae III, Pvu II [8], indicated that this BLV sequence was identified as Genotype 1. On the other hand, phylogenetic analysis in this study and other previous studies demonstrated that this sequence fell in cluster of Genotype 6 [7, 16, 19]. In spite of these misidentifications, identifications of new genotypes such as Genotype 9 in Bolivia and Genotype 10 in Thailand and Myanmar [7, 16] led to the development of a modified, broadly applicable PCR-RFLP method.…”
mentioning
confidence: 48%